PENGARUH PENGGUNAAN PENDEKATAN KETERAMPILAN PROSES DALAM MENINGKATKAN KEMAMPUAN MENGAPRESIASI PUISI SISWA KELAS VIII DI SMP 11 KOTA MAKASSAR - Herawati Arief S; Jayanti Sampara (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2019)
Abstract: The Effect of Process Skill Approach in Improving the Ability of Poetry Appreciation in Class VIII Students at SMP 11 Makassar City. This research aimed to describe the application of the process skill approach and find out the effectiveness of process skill approach in improving the ability of poetry appreciation in class VIII students at SMP 11 Makassar City. The method used in this research was experimental method consisted of two groups, namely experimental and control class. The research used two variables: the independent variable, namely the process skill approach and the dependent variable, namely the conventional teaching model applied at the school. Data collection in this research was carried out through test and analyzed using descriptive and inferential statistics through SPSS version 20. The results of this research indicated the effectiveness of process skill approach in improving of poetry appreciation learning based on the hypothesis. The alternative hypothesis (HI) is accepted if the value of t is calculated> value of t table. Conversely, HI is rejected if the calculated t value <table t value. In other words, the hypothesis is accepted if the t value is greater than or equal to t table at a significant level of 5%. Or the t value was 5.186> 2.04 t table. This showed that the process skill approach was effectively applied in increasing the ability to appreciate poetry.